Neoribates alius Fujikawa, 2007, a junior synonym of Neoribates pallidus Aoki, 1988 (Acari, Oribatida, Parakalummidae) - Ermilov, Sergey G.; Salavatulin, Vladimir M.; Kaga, Wataru; Shimano, Satoshi (Zootaxa, 2014)
The morphology of adult instars of two oribatid mites of the genus Neoribates, N. pallidus Aoki, 1988 and N. alius Fujikawa, 2007, is analyzed. Comparisons were based on holotype and paratypes (for N. alius) and specimens identified by the original author (for N. pallidus). Both species were described from Japan. Neoribates alius is recognized as a junior subjective synonym of N. pallidus.